1992
DOI: 10.1128/jcm.30.9.2447-2450.1992
|View full text |Cite
|
Sign up to set email alerts
|

Acanthamoeba keratitis: synergy between amebic and bacterial cocontaminants in contact lens care systems as a prelude to infection

Abstract: We encountered a patient with Acanthamoeba keratitis whose contact lens care solution contained numerous trophozoites and cysts admixed with Xanthomonas maltophilia organisms, many of which were adherent to the trophozoite surface and internalized within endocytic vacuoles. Because of this finding, we investigated the role of bacterial cocontaminants in contact lens care systems as substrates for the growth of Acanthamoeba spp. Individual cocultivation of Acanthamoeba castellanii and A. polyphaga with X. malto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(23 citation statements)
references
References 13 publications
1
19
0
3
Order By: Relevance
“…Several Gram negative bacterial species such as E. coli, Xanthomonas maltophilia, Flavobacter breve and Pseudomonas paucimobilis have been shown to support the growth of Acanthamoeba, while Ps. aeruginosa has been shown to inhibit Acanthamoeba growth (Bottone et al 1992). In our study, we observed a dual pattern.…”
Section: Discussionsupporting
confidence: 63%
“…Several Gram negative bacterial species such as E. coli, Xanthomonas maltophilia, Flavobacter breve and Pseudomonas paucimobilis have been shown to support the growth of Acanthamoeba, while Ps. aeruginosa has been shown to inhibit Acanthamoeba growth (Bottone et al 1992). In our study, we observed a dual pattern.…”
Section: Discussionsupporting
confidence: 63%
“…First, the concept of frequent replacement and disposable soft lenses has greatly reduced the incidence of complications associated with lens spoilage and contamination 30,31 . Second, there is a belief that effective bacterial disinfection by a given contact lens storage solution removes a significant potential ‘food’ for Acanthamoeba and, therefore, provides indirect protection 32 . Third, while the contact lens case biofilm can provide Acanthamoeba with significant bacterial protection against disinfection, 15 frequent replacement of the contact lens case is now more common in clinical practice and there has been the development of contact lens cases incorporating antimicrobial agents 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the presence of potential pathogen sequences indicated occasional distribution and dispersion of pathogens in cloud water ( Table 3). The identified opportunistic pathogens from Empedobacter, e.g., E. brevis, can easily be isolated from clinical resources, which may be associated with eye infections (Bottone et al, 1992). Occurrences of Staphylococcus equorum in cloud water can be expected since Staphylococcus are frequently isolated from airborne samples (Seo et al, 2008).…”
Section: Implications For Human Health and The Ecosystemmentioning
confidence: 99%